Research on the History of Pedagogy in Lithuania: an Analysis of Publications in Acta Paedagogica Vilnensia - Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2016)
The article aims to analyze how the ideas of history of education are reflected in the publication of the journal Acta Paedagogica Vilnensia. By applying the method of content analysis, the content of publications on history of education is discussed together with its changing tendencies and methodological approaches. Having counted the publications in the journal since 1991, it was established that articles dealing with historical aspects of education comprise one tenth of all publications (N563). However, their distribution is very unequal. In the first stage of the journal publishing (1991–2000), the interest in the history of education and in the works written by interwar Lithuanian educators, also in the evolution of institutions – the New Education movement in particular – was highly obvious. The articles on history of education comprise 23.7% of all (N135) publications. However, the percentage of such articles published later undergoes a considerable decline: from 2001 to 2009, it equals 7.4% of all articles (N296), whereas in the third stage (since 2010 to present) it barely reaches 3.7%. It is hard to state whether such tendency has been predetermined by a decreasing popularity of history of education all over the world or by the fact that a strong school of history of education, whose representatives would either discuss theoretical and methodological approaches to history of education or apply more diverse research methods, etc., has never been established in Lithuania.
Keywords: ...